Sexually transmitted infections and sexually transmitted diseases - Gross, G. (Gerd); Tyring, Stephen K. (Springer Verlag, 2011)
This comprehensive, up-to-date reference book is intended to serve as the standard guide in the field. It covers the epidemiology and etiology of the various sexually transmitted infections and associated diseases, reviews novel diagnostic methods, and discusses in depth both new and established treatment methods. An important part of the book is devoted to prevention and particularly to immunoprevention by vaccination. Related issues such as sexual abuse, psychosocial aspects, and economic and political considerations are also included. The expertise of many worldwide renowned specialists and superb color illustrations make this book a valuable resource for practitioners from a variety of medical disciplines. It has a reader-friendly structure with core messages and take-home pearls.